1985
DOI: 10.1093/ajcn/42.5.1099
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous opioid peptides and regulation of drinking and feeding

Abstract: Considerable work across the last 10 yr has implicated the endogenous opioid peptides in the regulation of ingestion. The opioid antagonists, such as naloxone and naltrexone, reduce intake of water, flavored water, and food. Naloxone's effects are pharmacologically specific, ie, its effects are dose-related and stereoselective. Further, a variety of antagonists produce similar effects. A primary site of action of naloxone, with respect to intake, is in the central nervous system. Naloxone's effects are also be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
0
2

Year Published

1988
1988
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(65 citation statements)
references
References 161 publications
5
58
0
2
Order By: Relevance
“…In addition, in cocaine-trained rats, Lu and Dempsey (2004) found that heroin had greater effects later in abstinence vs early on reinstating cocaine seeking behavior-a cross-sensitivity suggesting that either the DA or opiate system (or both) is altered over the incubation of craving. DA release in the nucleus accumbens (NAcc) is increased/decreased by microinjection of an opiate agonist/antagonist into the ventral tegmental area (VTA; Spanagel et al 1992;Devine et al 1993) and endogenous opiates mediate food intake in rats (Reid 1985) including motivation to consume food (Glass et al 1999). Therefore, as we have observed an effect of forced abstinence on DA sensitivity related to responding for a sucrose-paired cue (Grimm et al 2006), we hypothesized that we would also see a time-dependent effect of a manipulation to affect the opiate system on responding for a sucrose-paired cue.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in cocaine-trained rats, Lu and Dempsey (2004) found that heroin had greater effects later in abstinence vs early on reinstating cocaine seeking behavior-a cross-sensitivity suggesting that either the DA or opiate system (or both) is altered over the incubation of craving. DA release in the nucleus accumbens (NAcc) is increased/decreased by microinjection of an opiate agonist/antagonist into the ventral tegmental area (VTA; Spanagel et al 1992;Devine et al 1993) and endogenous opiates mediate food intake in rats (Reid 1985) including motivation to consume food (Glass et al 1999). Therefore, as we have observed an effect of forced abstinence on DA sensitivity related to responding for a sucrose-paired cue (Grimm et al 2006), we hypothesized that we would also see a time-dependent effect of a manipulation to affect the opiate system on responding for a sucrose-paired cue.…”
Section: Introductionmentioning
confidence: 99%
“…Women with abdominal obesity are characterized by several hormonal and metabolic abnormalities including moderate to severe hyperinsulinaemia and insulin resistance, 9,10 impaired glucose tolerance, 10 altered sex hormone metabolism, 11 hyperactivity of the hypothalamic pituitary adrenal axis 12 and an increased opioid activity, 13,14 which could be part of a more complex neuroendocrine alteration. Several studies have provided evidence that endogenous opioids seem to play a role in the pathogenesis of human obesity 15,16 since they are involved in the regulation of food intake 17,18 and of insulin secretion. 19卤21 Furthermore, endogenous opioids might play a physiological role in the regulation of glucose homeostasis by the central nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…An i.v. bolus of 50% glucose (0.3 g/kg) was injected at time 0 (over 1 min exactly), followed by a normal saline infusion and subsequent samples were drawn at 2, 3,4,5,6,8,10,12,14,16,18,20,22,23,24,25,27,28,30,35,40,45,50,55,60,70,80,90, 100, 120, 140, 160 and 180 min.…”
mentioning
confidence: 99%
“…Moreover, the reduction in alcohol self-administration seen with compound 5 was selective, because at efficacious doses, compound 5 did not affect consumption of water or Supersac. This is important because some opioid receptor antagonists decrease both ethanol and sucrose intake in rats (Pastor and Aragon, 2006) or inhibit energy-rich food consumption (Reid, 1985). It may be that opioid receptor antagonists prevent central reward mechanisms that may share common neural substrates responsible for the development of alcohol dependence (Yeomans and Gray, 2002).…”
Section: Potent Alcohol Cessation Agentsmentioning
confidence: 99%